2022
DOI: 10.12998/wjcc.v10.i29.10583
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiome changes in an infant with right atrial isomerism and recurrent necrotizing enterocolitis: A case report and review of literature

Abstract: BACKGROUND Necrotizing enterocolitis (NEC) is a multifactorial disease that predominantly affects premature neonates. Intestinal dysbiosis plays a critical role in NEC pathogenesis in premature neonates. The main risk factor for NEC in term infants is mesenteric hypoperfusion associated with ductal-dependent congenital heart disease (CHD) that eventually leads to intestinal ischemia. The incidence of NEC in neonates with critical CHD is 6.8%-13%. However, the role of the intestinal microbiome in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Knowledge about the gut microbiome of infants with CHD is only beginning to emerge, 62 , 63 , 64 , 65 , 66 , 67 and there has been no investigation into HM composition in the context of CHD. A 2022 study by Huang et al 62 provided the first comprehensive evidence on the gut microbiome of neonates with critical CHD, reporting dysbiosis characterized by increased pathogens (eg, Enterococcaceae , Enterobacteriaceae ) and decreased beneficial organisms (eg, Bifidobacterium , Lactobacillus ), a profile that shares similarities with the gut microbiome of very‐low‐birth‐weight infants, 58 with consequent inflammatory and immune imbalances potentially contributing to poor clinical outcomes, including NEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about the gut microbiome of infants with CHD is only beginning to emerge, 62 , 63 , 64 , 65 , 66 , 67 and there has been no investigation into HM composition in the context of CHD. A 2022 study by Huang et al 62 provided the first comprehensive evidence on the gut microbiome of neonates with critical CHD, reporting dysbiosis characterized by increased pathogens (eg, Enterococcaceae , Enterobacteriaceae ) and decreased beneficial organisms (eg, Bifidobacterium , Lactobacillus ), a profile that shares similarities with the gut microbiome of very‐low‐birth‐weight infants, 58 with consequent inflammatory and immune imbalances potentially contributing to poor clinical outcomes, including NEC.…”
Section: Discussionmentioning
confidence: 99%
“… 62 The authors propose Bifidobacterium and oligosaccharide supplementation for infants with critical CHD but stop short of recommending improved lactation support for these infants and their families as a mechanism to promote intestinal homeostasis. Of the remaining abstracts, 67 studies, 63 , 65 , 66 or reviews 64 identified on the topic of the gut microbiome in patients with CHD, only 1 briefly mentions HM/breastfeeding, 66 and none discuss HM/breastfeeding as a therapeutic intervention for gut dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about the gut microbiome of infants with CHD is only beginning to emerge, [64][65][66][67][68][69] and there has been no investigation into HM composition in the context of CHD. A 2022 study by Huang et al.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…64 The authors propose Bifidobacterium and oligosaccharide supplementation for infants with critical CHD, but stop short of recommending improved lactation support for these infants and their families as a mechanism to promote intestinal homeostasis. Of the remaining abstracts, 69 studies, 65,67,68 or reviews 66 identified on the topic of the gut microbiome in patients with CHD, only one briefly mentions HM/BF 68 and none discuss HM/BF as a therapeutic intervention for gut dysbiosis.…”
Section: Potential Mechanismsmentioning
confidence: 99%